+0  
 
0
174
1
avatar+2448 

Plz help, ty!

 Apr 26, 2018
 #1
avatar+98197 
+2

This one is a litle  tricky, RP

 

x^2 - 12 x + 49  = 22      subtract 22 from  both sides

 

x^2 - 12x + 27  = 0        we need two  numbers that su to -12 and multiply to 27...-9 and -3  fit the bill...so we have

 

(x - 9) ( x - 3)  = 0

 

Setting these to 0 and solving for x  produces   x  = 9   and  x  = 3

 

Look at   "A"

If  x = 9, we have     (9- 6)^2  =   3^2  = 9    

And if x = 3 , we have     (3-6)^2  = (-3)^2  = 9

 

So....that must be the correct  one   !!!!

 

Does that make any sense.....???

 

Another way to do this is to expand each answer....note that

 

(x - 6)^2  = 9   becomes

 

(x - 6) ( x - 6)  = 9

 

x^2  - 12x + 36  = 9

 

x^2 - 12x + 27  = 0    which is the same equation we found initially (in red, above)....so....they must have the same solutions  !!!

 

cool cool cool

 Apr 26, 2018

34 Online Users

avatar
avatar
avatar